INNOVATIVE PEDAGOGICAL ACTIVITY OF THE FUTURE IT TEACHER - Ziyayev son of Sherali Abdulaziz (Galaxy International Interdisciplinary Research Journal, 2023)
This article is devoted to the problem of forming the ability of the future informatics teacher to use it from a conscious and critical point of view in the innovative pedagogical professional activity.